Model of flipped classroom environment for mastery learning approach using the “ZOOMRBT App” - Noor Izwan Nasir; Marina Ibrahim Mukhtar (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the digital era that encourages innovation in educational technology, it is crucial to incorporate the use of technology into pedagogy. Since the inception of hybrid learning and other approaches that involve students and instructors in educational activities, the learning environment has undergone significant changes. By utilizing instructional resources such as textbooks and videos, it has become feasible to engage with students beyond the confines of the classroom and during evening hours. Research conducted on students in grades 8 and 9 in Ontario, Canada, revealed that due to their limited spare time, they opted to study and complete their homework after school. Moreover, they exhibited a clear prioritization of their depth of subject knowledge over other factors. The study aimed to adapt the existing learning environment to establish a new environment conducive to mastery learning. It involved fifteen student participants, including an expert teacher in the flipped classroom teaching method. The study employed qualitative techniques such as focus groups, document analysis, expert agreement percentages, and innovative flipping of the classroom. The study resulted in the identification of five thematic analyses: learning flexibility, application skills, usage of application skills, mastery assessment, and the human touch. Collectively, these qualitative findings provide compelling evidence that the research participants actively engage with various aspects of the flipped learning environment, as outlined by the aforementioned themes. The participants in the case study acted as both fresh and established elements within the flipped learning environment.